Semiconductor Laser Dynamics Fundamentals and Applications - Lenstra, Daan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This is a collection of 18 papers, two of which are reviews and seven are invited feature papers, that together form the Photonics Special Issue "Semiconductor Laser Dynamics: Fundamentals and Applications", published in 2020. This collection is edited by Daan Lenstra, an internationally recognized specialist in the field for 40 years.